Gagasan Penataan Pilkada Calon Tunggal - Junaidi - Junaidi (Jurnal Penelitian Hukum De Jure, 2023)
The existence of single candidate in the 2015-2020 simultaneous Local Election (Pilkada) period tends to dramatically increase along with the rise of the political parties coalition supporting single candidate, thus closing the opportunity for other candidates to advance through a political party. In the practice of organizing single-candidate elections, several cases have been exposed to the public, which suggests that there were problems before the single candidate was decided. This study describes the various phenomena that arise in the organization of single-candidate elections and formulates appropriate structuring strategies. This research was normative and sociological legal research. Normatively using a statute approach and case approach, while sociologically using a qualitative approach. Several phenomena were found, namely; the increasing support of political parties for single candidate is due to the pragmatic political parties that are oriented towards victory and instant profit (political dowry), resulting in a large financial burden that must be prepared by prospective candidates. This condition is exceptionally favorable for candidates with sufficient financial capabilities which then motivates political parties to smooth the victory. Appropriate structuring measures are needed, including; first, the need to reduce the nomination threshold for political parties. Second, organizing party coalitions both related to the time of formation and the maximum limit of the coalition, and third, tightening the eligibility requirements for single candidate by considering the level of voter turnout.